Gearbox power loss. Part III: Application to a parallel axis and a planetary gearbox. (August 2015) - Fernandes, Carlos M.C.G.; Marques, Pedro M.T.; Martins, Ramiro C.; Seabra, Jorge H.O.
Abstract: In the third part of this work, the rolling bearing torque loss model, the lubricant factor extracted from the FZG tests with wind turbine gear oils and the loss factor for helical gears, developed in Part I and Part II of this work, will be applied to predict the power loss in a parallel axis and a planetary gearbox. The numerical results obtained are compared with those from experimental tests. Abstract : Highlights: Power loss in gearboxes lubricated with wind turbine gear oils. Test rig with recirculating power. Comparison between numerical predictions and experimental results at stabilized operating conditions.